Combination Laser Treatment With Real-Time Ultrasound Navigation for Oral Venous Malformations. Issue 8 (November 2020) - Noguchi, Tadahide; Konno, Yu; Sugiura, Yasushi; Dohi, Akihiro; Okada, Naruo; Sasaguri, Ken-ichi; Oyatsu, Yukio; Fujita, Akifumi; Miyazaki, Hidetaka; Mori, Yoshiyuki
Abstract : Abstract: Vascular lesions, including hemangiomas and vascular malformations, are common benign diseases. More than 50% originate from blood vessels or vascular structures and are locate in the head and neck region. This study aimed to evaluate the efficiency and safety of a combination of laser treatments for oral venous malformations using ultrasound navigation. This study reports 3 cases of massive vascular malformation in the oral cavity, which were treated by a combination of a multiple spotted transmucosal irradiation technique (the so-called leopard technique) for the superficial layer, and intralesional photocoagulation for the deep layer using a neodymium-doped yttrium aluminum garnet laser, under real-time ultrasound navigation. All cases presented with a venous malformation with multiple blue swellings on the dorsum of the tongue, which had a maximum dimension of over 30 mm. The percent reduction in the size of the lesions was determined by magnetic resonance imaging. All cases showed a decrease in lesion volume of over 80%, without extensive tissue necrosis, 6 to 12 months after the laser treatment. None of the patients experienced any complications, and all were satisfied with the treatment outcome after one irradiation session. The results of this study suggest that laser treatment using ultrasound navigation is a promising approach for the safe and minimally invasive resolution of oral vascular lesions without scarring and loss of normal tissue architecture, sensation, oral function.